5(4-3t)=-40

Simple and best practice solution for 5(4-3t)=-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4-3t)=-40 equation:


t in (-oo:+oo)

5*(4-(3*t)) = -40 // + 40

5*(4-(3*t))+40 = 0

5*(4-3*t)+40 = 0

5*(4-3*t)+40 = 0

60-15*t = 0

60-15*t = 0

60-15*t = 0 // - 60

-15*t = -60 // : -15

t = -60/(-15)

t = 4

t = 4

See similar equations:

| .6x=.8+2.4 | | 6(-5t-1)=-336 | | 6(-6n-8)=96 | | 7(5t-4)=112 | | 5(-7t-6)=-170 | | 7(5k+4)=-7 | | 6x+9=2x | | 2x^3-5x^2+6x-15=0 | | 6(1+7k)=384 | | 6(-2)-3y=12 | | 2x+2(2x-3)=48 | | 7(-5+3d)=175 | | 7(-10+4b)=-322 | | 8(3x-11)=32 | | 2x-f=12 | | 3(5+4a)=63 | | 4(5+6d)=-28 | | 4(2w+7)=124 | | 6(2)-3y=12 | | 3(-6+6m)=-18 | | 2(-7-2x)=-2 | | 5(-9+4k)=135 | | 3(4+5w)=87 | | 4(3-2k)=12 | | 2(1+7k)=58 | | y+2(-2)=-8 | | 15+x=4x | | y+2(0)=-8 | | 4(1a-7)=-24 | | 6(9-x)=42 | | 6(-7+3n)=48 | | 5(6-3a)=135 |

Equations solver categories